2018
DOI: 10.7759/cureus.3202
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Paraneoplastic Guillain-Barré Syndrome Associated with Squamous Cell Carcinoma of the Lung

Abstract: We report a case of a 61-year-old man with a history of squamous cell carcinoma of the lung presenting with rapidly progressive symmetric ascending weakness with areflexia. The weakness was quickly followed by respiratory decompensation requiring intubation. Lumbar puncture yielded cerebrospinal fluid with elevated protein (177 mg/dL), normal glucose (61 mg/dL), normal red blood cell count (0 per/µl), and normal white blood cell count (0 per/µL). Emergent magnetic resonance imaging of cervical, thoracic, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Previous case-reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and small cohort studies, 19,20 as well as the recent case-control study, 3 have reported cancers before, concomitantly with, and shortly after the diagnosis of GBS. These diverse approaches complicate the interpretation of the association, in terms of directionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous case-reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18] and small cohort studies, 19,20 as well as the recent case-control study, 3 have reported cancers before, concomitantly with, and shortly after the diagnosis of GBS. These diverse approaches complicate the interpretation of the association, in terms of directionality.…”
Section: Discussionmentioning
confidence: 99%
“…31 The magnitude of risk and prevalence of small cell and non-small cell lung cancer in our GBS cohort, as well as results from past case reports, align with this evidence. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] A potential mechanism underlying the association between GBS and cancer is based on the observation that the cross-immunoreaction involving the tumor and peripheral nerves is caused by the presence of high levels of anti-GM1 ganglioside IgG autoantibodies, anti-Hu, and onconeural antibodies targeting antigen-specific T-lymphocytes. 9 However, evidence of the presence of these markers in GBS patients with malignancies is inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the association between GBS and malignancy is still debated as Graus et al do not define it as a paraneoplastic syndrome in the absence of high-risk antibodies 9. A number of case reports described GBS in patients with an existing or later diagnosed malignancy12–25 and a small number of population-based studies have identified an increased risk of cancer in patients who developed GBS 8 26 27. Nevertheless, it is not clear whether these findings demonstrate an actual causal link or simply two separate concurrent diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Guillain-Barre Syndrome has been reported as a rare paraneoplastic syndrome, primarily in the setting of lung cancer and lymphoma. Notably, in several of these cases, antibody testing was negative [2][3][4][5]. It is unclear why certain malignancies have a greater predisposition to paraneoplastic syndromes.…”
Section: Introductionmentioning
confidence: 99%